Variation in competent and respectful delivery care in Kenya and Malawi: a retrospective analysis of national facility surveys. Issue 4 (2nd January 2020) - Arsenault, Catherine; English, Mike; Gathara, David; Malata, Address; Mandala, Wilson; Kruk, Margaret E.
Abstract: Objective: Although substantial progress has been made in increasing access to care during childbirth, reductions in maternal and neonatal mortality have been slower. Poor‐quality care may be to blame. In this study, we measure the quality of labour and delivery services in Kenya and Malawi using data from observations of deliveries and explore factors associated with levels of competent and respectful care. Methods: We used data from nationally representative health facility assessment surveys. A total of 1100 deliveries in 392 facilities across Kenya and Malawi were observed and quality was assessed using two indices: the quality of the process of intrapartum and immediate postpartum care (QoPIIPC) index and a previously validated index of respectful maternity care. Data from standardised observations of care were analysed using descriptive statistics and multivariable random‐intercept regression models to examine factors associated with variation in quality of care. We also quantified the variance in quality explained by each domain of covariates (patient‐, provider‐ and facility‐level and subnational divisions). Results: Only 61–66% of basic elements of competent and respectful care were performed. In adjusted models, better‐staffed facilities, private hospitals and morning deliveries were associated with higher levels of competent and respectful care. In Malawi, younger, primipara and HIV‐positive women received higher‐quality care. Quality also differed substantially across regions in Kenya, with a 25 percentage‐point gap between Nairobi and the Coast region. Quality was also higher in higher‐volume facilities and those with caesarean section capacity. Most of the explained variance in quality was due to regions in Kenya and to facility, and patient‐level characteristics in Malawi. Conclusions: Our findings suggest considerable scope for improvement in quality. Increasing staffing and shifting births to higher‐volume facilities – along with promotion of respectful care in these facilities – should be considered in sub‐Saharan Africa to improve outcomes for mothers and newborns. Abstract : Objectif: Bien que des progrès substantiels aient été accomplis dans l'amélioration de l'accès aux soins pendant l'accouchement, les réductions de la mortalité maternelle et néonatale ont été plus lentes. Des soins de mauvaise qualité peuvent être à blâmer. Dans cette étude, nous mesurons la qualité de la main‐d'œuvre et des services d'accouchement au Kenya et au Malawi en utilisant les données des observations des accouchements et explorons les facteurs associés aux niveaux de la compétence et du respect dans les soins. Méthodes: Nous avons utilisé les données d'enquêtes d'évaluation des établissements de santé représentatives au niveau national. 1100 accouchements dans 392 établissements au Kenya et au Malawi ont été observés et la qualité a été évaluée à l'aide de deux indices: l'indice de qualité du processus de soins intra‐partum et postpartum immédiat (QoPIIPC) et un indice précédemment validé de soins maternels respectueux. Les données des observations normalisées des soins ont été analysées à l'aide de statistiques descriptives et de modèles de régression à interceptions aléatoires multivariables pour examiner les facteurs associés à la variation de la qualité des soins. Nous avons également quantifié la variance de la qualité expliquée par chaque domaine de covariables (divisions au niveau des patients, des prestataires et des établissements, et infranationales). Résultats: Seuls 61% à 66% des éléments de base de soins compétents et respectueux ont été réalisés. Dans les modèles ajustés, des établissements mieux dotés en personnel, des hôpitaux privés et des accouchements le matin étaient associés à des niveaux plus élevés de soins compétents et respectueux. Au Malawi, les femmes plus jeunes, primipares et VIH positives ont reçu des soins de meilleure qualité. La qualité différait également considérablement d'une région à l'autre au Kenya, avec un écart de 25 points de pourcentage entre Nairobi et la région côtière. La qualité était également plus élevée dans les établissements avec un volume plus élevé et ceux ayant une capacité de césarienne. La majeure partie des raisons de la variance dans la qualité était liée aux régions du Kenya et à l'établissement et aux caractéristiques des patients au Malawi. Conclusions: Nos résultats suggèrent une marge considérable pour l'amélioration de la qualité. L'augmentation du personnel et le déplacement des naissances vers des établissements de plus grand volume – ainsi que la promotion de soins respectueux dans ces établissements – devraient être envisagés en Afrique subsaharienne pour améliorer les résultats pour les mères et les nouveau‐nés.